SUSTAINABLE PLASTIC WASTE MANAGEMENT- A CASE STUDY OF THANE MUNICIPAL CORPORATION - Prof. T. Z. Quazi; Prof. M. D. Jagtap (International Journal of Innovations in Engineering Research and Technology, 2021)
Thane Municipal Corporation is located near to Mumbai City in Maharashtra State of India. Thane is growing rapidly since last few decades. The total area of Thane city is 128 Sq. Km. According to census 2011, total Population of city is 18.41 Lakhs and floating population is about 3 lakhs. The Solid Waste generation in the TMC area is around 650 MT per day. Out of which Plastic waste generation is about 60-70 MT per day. TMC don’t have any system for processing this plastic waste. This paper suggests a sustainable and one of the most emerging technologies of Plastic waste pyrolysis to TMC. Plastic Waste Pyrolysis is an ideal technology which is eco-friendly as well as generates furnace oil, carbon and hydrocarbon gas as productive output.